DISEÑO DE UN SISTEMA CONTABLE A ACERSA FRANQUICIADO DISENSA DE LA CIUDAD DE LOJA, PERIODO ENERO – JUNIO 2015 - Sarango López Paulina Janeth (2016)
The thesis is made based on the needs of the company, it was raised as main objective "Designing an accounting system to Acersa Franchisee Disensa city of Loja, period January-June 2015," thus allowing the company to have a proper record of all your tranascciones and thus meet the economic and financial situation of the same. For the development of the research the following specific objectives: The first objective was to organize the inventory of Goods, to know the real value that has Disensa Acersa Franchisee; To comply with it, the Inventory of Goods was organized for the actual value available to the company, this was achieved through the development of an extra-book inventory . Plan and Audit Manual which identifies the nature and dynamics of transactions in the proper use of the accounts was made. The second objective was to develop a Plan and Manual accounts to identify the nature of transactions Acersa Disensa Franchisee; For this, a Plan and Manual accounts that identified the nature and dynamics of the transactions of the organization, considering the needs and the type of activity performed by the company was developed. 5 The third objective was designed accounting system to record transactions to the presentation of financial statements Acersa Franchisee Disensa, using the registration and control system has múltiple merchandise; to achieve the same accounting system that allowed recording operations to the presentation of financial statements, where the economic situation being experienced by the company conocío was designed. The fourth specific objective was to apply financial indicators of liquidity, activity, profitability and debt, to point out the strengths and weaknesses of the company points, this was achieved by using financial indicators of liquidity, activity, profitability and debt, to highlight weaknesses and strengths of economic organization. It is concluded that the design of an accounting system for the company Acersa FRANCHISEE Disensa, served to present the economic situation of the same through the financial statements as: Statement of Financial Position, State Economic Situation, cash flow statement and State of Changes in Equity, for which the following recommendation is proposed; continue and monitor the accounting system designed, the same one that presents a clear and specific way to register accounting economic and financial activities, thereby transforming the process in monetary terms.